Misuse of medications in the treatment of dengue (Research, Society and Development, 2024)
The objective of this study is to analyze the impact of self-diagnosis and self-medication in the treatment of dengue. With the increasing number of cases of this disease in various regions of Brazil, the inappropriate use of medications without proper guidance from a healthcare professional is common, a practice that can lead to serious health consequences for the individual. The research involved a literature review and case analysis, addressing the main medications wrongly used by the population in an attempt to treat dengue. The study also investigates the reasons leading to this risky practice, such as lack of adequate information, difficulty accessing medical care, and belief in the efficacy of these medications. The central question of the research is: What are the health risks for the population in using inappropriate medications in the treatment of dengue? The answer to this question is sought through the identification of the main problems arising from this practice, such as adverse reactions, dangerous drug interactions, and even worsening of the clinical condition. The results obtained point to the urgent need for educational campaigns on the dangers of self-medication and clear guidance on the appropriate treatment for dengue. Furthermore, the crucial role of pharmacists in educating the population about the correct use of medications is emphasized. This work, therefore, aims to contribute to raising awareness about the serious problem of self-medication in the treatment of dengue, a topic that requires constant attention from health authorities and the general population alike.